Strength and Durability Characteristics of Steel Fibre Reinforced Geopolymer Concrete - Jessy Magdalene Anna, J; . Sumathi, A (International Journal of Engineering and Technology, 2018)
Owing to the upturn inrepair and rehabilitation of structures that undergoes deterioration even before its intended life span; it has become necessary to study the durability properties of the structures. This paper deals with an experimental approach on the strength and durability characteristics of Geopolymer Concrete and Steel Fibre Reinforced Geopolymer Concrete with varying proportions of Fly ash, Waste Glass powder and GGBS (Ground Granulated Blast furnace Slag) as base material cured at room temperature. Sodium hydroxide (14M) and Sodium silicate are used as alkali activators. Steel fibres of length 60mm, 0.75mm diameter are used in two different proportions (0.25% and 0.50%). The results are compared with that of the Portland cement based plain and fibre reinforced control concrete. The durability characteristic involved in this study is Sorptivity test. The results reveal that Steel fibre reinforced Geopolymer concrete procures surpassing characteristics than that of Geopolymer concrete which in turn possess superior characteristics than that of conventional concrete.Â Â